Kajian Surat Al-Baqarah Ayat 183 dalam Pendidikan Manusia Seutuhnya - Kholiq, Abd.; Shofiyah (rogram Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI) Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2022)
Fulfillment of education is essentially to harmonize between the rights of God and the rights of fellow human beings so that it runs well in accordance with His expectations. In life, of course, it cannot be separated from the right and left slaps that make humans fall or rise according to the human capacity itself regardless of who runs it, it is from the selection of the social community. In the letter al-Baqarah verse 183 describes the methods or means in learning media that Allah directly gives the signs and criteria given in order to achieve what is expected. Therefore, in the process of implementing this fast, Allah directly controls the implementation to humans which has been given by Allah several criteria that can make the implementation of this education successful. The key words that God gave to humans in the shell of giving education to get to piety are people of faith. This is the success of how to carry out this education according to the criteria given by God, for those who carry out to achieve taqwa learning as the key to the success of whole person education (kaffah).